Analisis Stilistika Pada Puisi Tuhan Harus Mengabdi Karya Emha Ainun Nadjib - Dania Kusuma Wardani; Wawan Hermawan; Tiwi Widya Lestari; Misbahul Khanif (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The power of poetry is its ability to arouse reflection in the reader. Poetry has its own characteristics that distinguish it from prose, especially through the use of language. This study aims to analyze the stylistics in the poem Tuhan Harus Mengabdi by Emha Ainun Nadjib. Through a stylistic approach, the analysis is directed at examining diction, imagery, concrete words, figurative language, rhyme and rhythm, theme, feelings, tone, and message. The working method in this study uses a descriptive qualitative method, which focuses on the appreciation of the interaction between concepts that are studied empirically. While the collection technique uses literature studies. The results of the study reveal that the poem Tuhan Harus Mengabdi processes religious-nuanced diction that builds concrete images of spiritual and social relations. The use of figurative language, such as metaphors and personification, becomes a medium for voicing criticism of the hierarchical structure in faith. The flexible rhyme and rhythm patterns blend with emotional intensity, anger and disappointment have been raised through feelings while the theme, tone, and message spark human ethical responsibility. This research is expected to add to the research treasury and become a reference for further research.